2019
DOI: 10.1029/2018jg004771
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration Components and their Temperature Sensitivity Under Chemical Fertilizer and Compost Application: The Role of Nitrogen Supply and Compost Substrate Quality

Abstract: Understanding autotrophic (Ra) and heterotrophic (Rh) components of soil respiration (Rs) and their temperature sensitivity (Q10) is critical for predictingsoil carbon (C) cycle and its feedback to climate change. In agricultural systems, these processes can be considerably altered by chemical fertilizer and compost application due to changes in nitrogen (N) supply and substrate quality (decomposability). We conducted a field experiment including control, urea, and four compost treatments. Ra and Rh were separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 88 publications
1
1
0
Order By: Relevance
“…The effect of compost on Rs also depends on the composition and quality of the compost, which means, e.g. amount of dissolved organic C, lignin, minerals, or C:N ratio (Chen et al, 2019;Ma et al, 2019). The temporality of the compost amendment on Rs was also confirmed in previous studies.…”
Section: Effect Of Treatment With Biochar Compost and Composted Biocharsupporting
confidence: 72%
See 1 more Smart Citation
“…The effect of compost on Rs also depends on the composition and quality of the compost, which means, e.g. amount of dissolved organic C, lignin, minerals, or C:N ratio (Chen et al, 2019;Ma et al, 2019). The temporality of the compost amendment on Rs was also confirmed in previous studies.…”
Section: Effect Of Treatment With Biochar Compost and Composted Biocharsupporting
confidence: 72%
“…Newly available organic C can be rapidly decomposed by microorganisms resulting in an increase in Rs as observed, e.g. by Wilson et al (2018) or Chen et al (2019). The effect of compost on Rs also depends on the composition and quality of the compost, which means, e.g.…”
Section: Effect Of Treatment With Biochar Compost and Composted Biocharmentioning
confidence: 99%
“…The study suggested that the fractional contribution of R a to R s may be greater in boreal forests than in temperate forests, reflecting regional differences in ecosystem dynamics [39]. These study findings contribute to our understanding of the variation in R a and R h contributions to R s , highlighting a multitude of factors influencing these dynamics with the potential to exhibit regional distinctions [40].…”
Section: Discussionmentioning
confidence: 67%
“…Applying inorganic fertilizers mixed with organic fertilizers and the temperature changes due to pruning heavily influencing soil respiration, specifically autotrophic respiration. Applying N fertilizer (inorganic fertilizers) increases root biomass, even in a small dose, and triggers autotrophic respiration (Chen et al 2017), due to root exudates secretion and microbial activity in the soil to decompose OM (Chen et al 2017(Chen et al , 2019. Heterotrophic respiration is suspected as a main driver, which determines soil respiration due to the given management at 20-40 cm depth.…”
Section: ; Sheng Et Al 2022)mentioning
confidence: 99%